2005
DOI: 10.1161/01.atv.0000188508.40052.35
|View full text |Cite
|
Sign up to set email alerts
|

Production of Chemokines by Perivascular Adipose Tissue

Abstract: Objective-Obesity is associated with an increased risk for cardiovascular disease. Although it is known that white adipose tissue (WAT) produces numerous proinflammatory and proatherogenic cytokines and chemokines, it is unclear whether adipose-derived chemotactic signals affect the chronic inflammation in atherosclerosis. Methods and Results-Histological examination showed that perivascular WAT (pWAT) is in close proximity to vascular walls, particularly at sites that have a tendency to develop atherosclerosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
142
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 337 publications
(149 citation statements)
references
References 29 publications
3
142
0
4
Order By: Relevance
“…Ramshaw and Parums followed and confirmed this in 1990 1) . In recent years, several reports have been published about adventitis accompanying atherosclerosis 15,[17][18][19][20] , but no reports have tried to elucidate the transition of the distribution of infiltrating inflammatory cells in the adventitia with advancing atherosclerosis. In the present study, T lymphocyte marker (CD45RO, CD4, CD8)-positive cells decreased in type , which might suggest that the original inflammatory response subsided in type and different or other inflammatory stimuli were induced in type .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ramshaw and Parums followed and confirmed this in 1990 1) . In recent years, several reports have been published about adventitis accompanying atherosclerosis 15,[17][18][19][20] , but no reports have tried to elucidate the transition of the distribution of infiltrating inflammatory cells in the adventitia with advancing atherosclerosis. In the present study, T lymphocyte marker (CD45RO, CD4, CD8)-positive cells decreased in type , which might suggest that the original inflammatory response subsided in type and different or other inflammatory stimuli were induced in type .…”
Section: Discussionmentioning
confidence: 99%
“…Schwartz reported lymphocyte accumulation in the adventitia of atherosclerosis in 1962 16) . In recent years, reports have increased about adventitis accompanying atherosclerosis and it is still unclear whether B lymphocytes or T lymphocytes are dominant 1,15,[17][18][19][20] . The possibility remains of the transition of infiltrating cells as the type of atherosclerosis advances, but no reports have tried to elucidate the relationship between the stage of atherosclerosis and the distribution of inflammatory cells in adventitia in human atherosclerosis.…”
mentioning
confidence: 99%
“…In addition, the mRNA levels of secretory type II phospholipase A2 (sPLA2-IIA), an enzyme promoting the generation of more atherogenic low-density lipoproteins and phospholipid products in the artery wall and their retention of in the subendothelial space, have been found increased in EAT from CAD patients [18]. In CAD conditions, as shown by proteomic and secretome analyses, EAT-derived mediators are capable of inducing cell surface expression of adhesion molecules in monocytes and endothelial cells [44], and FFAs released by EAT in the proximity of coronary arteries can modulate vascular responsiveness to vasoactive agents [45]. Contrariwise, EAT anti-inflammatory and anti-atherogenic adipokines (adiponectin and adrenomedullin) are down-regulated in chronic CAD, and increase in intracoronary adrenomedullin levels has been reported only when hemodynamic conditions improve as after coronary revascularization [25,26] (Fig.…”
Section: The Clinical Relevance Of Eat In Coronary Artery Diseasementioning
confidence: 99%
“…3) Recent reports showed that periadventitial fat secretes various chemokines that might contribute to the progression of obesity-associated atherosclerosis. 4) Epicardial adipose tissue (EAT) is located in close proximity to coronary arteries. EAT has been reported to be a source of inflammatory mediators.…”
mentioning
confidence: 99%